2017
DOI: 10.1002/2017tc004574
|View full text |Cite
|
Sign up to set email alerts
|

Differential Exhumation and Crustal Tilting in the Easternmost Tianshan (Xinjiang, China), Revealed by Low‐Temperature Thermochronology

Abstract: The easternmost Tianshan forms the eastern extremity of the modern Central Asian Orogenic Belt and represents a key locality to investigate strain propagation from the Meso‐Cenozoic plate margins to the Eurasian interior. The Tianshan as a whole has been reactivated multiple times throughout the Meso‐Cenozoic, but the extent of these reactivation events is yet to be fully understood. This study applies apatite fission track and apatite (U‐Th‐Sm)/He thermochronology to the mountain ranges of the easternmost Tia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 83 publications
4
59
0
Order By: Relevance
“…The dashed line in A illustrates the proposed boundary of regions with different provenances for the Jurassic deposits according to Greene et al (). The scenario since the Cenozoic (d) was determined based on thermochronology studies conducted by Wang et al (), Zhu et al () and Gillespie et al (), as well as a topography analysis of the Turpan‐Hami basin by Pullen et al ()…”
Section: Discussion and Conclusion: Relief Evolution Of The Eastern Ntsmentioning
confidence: 99%
See 4 more Smart Citations
“…The dashed line in A illustrates the proposed boundary of regions with different provenances for the Jurassic deposits according to Greene et al (). The scenario since the Cenozoic (d) was determined based on thermochronology studies conducted by Wang et al (), Zhu et al () and Gillespie et al (), as well as a topography analysis of the Turpan‐Hami basin by Pullen et al ()…”
Section: Discussion and Conclusion: Relief Evolution Of The Eastern Ntsmentioning
confidence: 99%
“…Apatite fission‐track (AFT) ages presented by Wang, Li, Zhang, Liu, and Ma () illustrated that major uplift of the eastern Tian Shan occurred between 30 and 20 Ma, with uplift migrating from west to east. These results were challenged by Gillespie et al (), who suggested that the easternmost Tian Shan experienced two phases of rapid cooling during the Early to Middle Triassic and the Late Cretaceous. They also demonstrated that an initial planation surface formed during the Jurassic and was reworked during the Late Cretaceous (Gillespie et al, ).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations